2009
DOI: 10.1002/micr.20695
|View full text |Cite
|
Sign up to set email alerts
|

Reversed flow lateral circumflex femoral vessels as recipients for free fibular grafting in treatment of femoral head osteonecrosis

Abstract: Free fibular bone grafting is an effective treatment for early osteonecrosis of the femoral head in young patients. However, recipient vessels are often small rendering microvascular anastomosis difficult. We have developed a novel technique using retrograde flow through the branches of the lateral circumflex femoral artery to use the proximal end of the artery as the recipient vessel. A vessel diameter of up to 5 mm is obtained providing a good match with the peroneal vessels. We used this technique to perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Once the early postcollapse stage is reached, total hip arthroplasty provides consistent results; however, satisfactory results have also been demonstrated with bone-grafting [112][113][114][115][116][117][118][119][120][121][122][123][124][125] . If there are signs of degenerative acetabular changes, total hip arthroplasty is appropriate (Tables I and II, Fig.…”
Section: Table II Decision-making Hierarchymentioning
confidence: 99%
See 1 more Smart Citation
“…Once the early postcollapse stage is reached, total hip arthroplasty provides consistent results; however, satisfactory results have also been demonstrated with bone-grafting [112][113][114][115][116][117][118][119][120][121][122][123][124][125] . If there are signs of degenerative acetabular changes, total hip arthroplasty is appropriate (Tables I and II, Fig.…”
Section: Table II Decision-making Hierarchymentioning
confidence: 99%
“…In 2012, a report on the long-term results of vascularized bone-grafting in sixty-five precollapse hips noted that 60% (thirty-nine hips) had survived at a mean follow-up of fourteen years (range, 10.5 to 26.1 years) 225 . In a study on an alternative free fibular anastomosis technique to the lateral circumflex artery in ten hips, only one required total hip arthroplasty at a mean follow-up of fifty-three months 113 . In a study of thirty-one hips, Babhulkar demonstrated a survival rate of 97% (thirty hips) at five to eight years of follow-up after vascular pedicle grafting using iliac crest with deep circumflex iliac vessels 167 .…”
Section: Vascularized Bone-graftingmentioning
confidence: 99%
“…Numerous procedures have been proposed to treat this condition, including core decompression [1,6,18,19,24,29,47,49,58,63], vascularized grafts [3,5,7,8,20,27,28,30,39,50,61,66], and osteotomy [2,9,16,17,23,40,44,45,62]. The term ''core decompression'' represents a spectrum of procedures that may include one large core tract or multiple small tracts [25,32].…”
Section: Introductionmentioning
confidence: 99%
“…The term ''core decompression'' represents a spectrum of procedures that may include one large core tract or multiple small tracts [25,32]. Additionally, core decompression may be supplemented with a vascularized [3,5,7,8,20,27,28,30,39,50,61,66] or nonvascularized graft [21,29,34,46,52,64] or with electrical stimulation [52]. Marker et al [33] compared the core decompression procedures before 1992 and between 1992 and 2007 and found patients with collapse of the femoral head often have progression of disease after a femoral head-saving procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Using this method, a vessel diameter of 5 mm is obtained providing a good match with the peroneal vessels. 28 The ipsilateral fibula is exposed through a lateral incision, by a second surgical team working simultaneously with the hip team. The middle third of the fibula, containing the nutrient vessels is harvesting.…”
Section: Operative Techniquementioning
confidence: 99%